An assessment of the role played by local authorities in promoting politico - economic development in Zimbabwe : the case of Mutare City Council from 2008-2016. - Mubure, Tanyaradzwa R. (Midlands State University, 2020)
Local authorities ensure a national face at local level and are mandated to enhance development in its jurisdictional areas. The main thrust of the study is to assess the role of local authorities in promoting politico-economic development in Zimbabwe using City of Mutare as a case study. The study intended to meet the objectives which are to explore the legislative frameworks governing the operations of Mutare City Council, to critically analyse the role of Mutare city council in promoting politico-economic development, to discuss the financial mechanisms used by City of Mutare to back its operations, to explain the challenges being faced by Mutare City Council in fostering politico-economic development in Zimbabwe and lastly to proffer recommendations for enhancing the politico-economic development of local authorities. To this end, the study acknowledged the recognition of local authorities in the Zimbabwean constitution, however the Urban Council Act 29:15 and the Rural District Councils Act have some provisions which does not tally with the constitution thereby undermining local government’s autonomy hence leading to underdevelopment. The study also noted that in terms of political and economic development, Mutare City Council has a role to play. Political development has been enhanced through various means to include participation in local ward election. Local democracy has also been encouraged through citizen participation. Economically, the study noted that Mutare city council is failing to steer maximum development as evidenced by levels of unemployment, obsolete infrastructure amongst other factors. The study also identified and explained the challenges that are militating against the operations of Mutare City Council and they include rampant corruption within the organization, partisan politics, inadequate financial capacity and increasing urbanization. The study acknowledged the major internal and external sources of finance which back up Mutare City Council activities. Amongst them the research noted that the major sources of finance includes intergovernmental transfers for example ZINARA disbursement funds, revenue generated through various project, taxation and revenue collected from services being rendered to ratepayers. In an attempt to promote political and economic development through local authorities, the study proffers recommendations such as de-politicization, advocating transparency mechanisms to deter corruption, revising the legislative frameworks and having financial capacity mechanisms.